Interplay between rhizospheric Pseudomonas chlororaphis strains lays the basis for beneficial bacterial consortia - Villar-Moreno, Rafael; Tienda, Sandra; Gutiérrez-Barranquero, Jose A.; Carrión, Víctor J.; de Vicente, Antonio; Cazorla, Francisco M.; Arrebola, Eva (Frontiers in Plant Science, 2022)
Pseudomonas chlororaphis (Pc) representatives are found as part of the rhizosphere-associated microbiome, and different rhizospheric Pc strains frequently display beneficial activities for the plant. In this work we described the interactions between the rhizospheric Pc strains PCL1601 (01), PCL1606 (06) and PCL1607 (07) with a focus on their root performance. Differences among the three rhizospheric Pc strains selected were first observed in phylogenetic studies and confirmed by genome analysis, which showed variation in the presence of genes related to antifungal compounds or siderophore production, among others. Observation of the interactions among these strains under lab conditions revealed that 06 has a better adaptation to environments rich in nutrients, and forms biofilms. Interaction experiments on plant roots confirmed the role of the different phenotypes in their lifestyle. The 06 strain was the best adapted to the habitat of avocado roots, and 07 was the least, and disappeared from the plant root scenario after a few days of interaction. These results confirm that 2 out 3 rhizospheric Pc strains were fully compatible (01 and 06), efficiently colonizing avocado roots and showing biocontrol activity against the fungal pathogen Rosellinia necatrix. The third strain (07) has colonizing abilities when it is alone on the root but displayed difficulties under the competition scenario, and did not cause deleterious effects on the other Pc competitors when they were present. These results suggest that strains 01 and 06 are very well adapted to the avocado root environment and could constitute a basis for constructing a more complex beneficial SynCom associated with avocado plant roots.